2007
DOI: 10.1111/j.1532-5415.2007.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilators and Nootropics as Predictors of Dementia and Mortality in the PAQUID Cohort

Abstract: These results suggest that treatment with EGb 761 may increase the probability of survival in the elderly population. These findings need to be corroborated and further assessed using randomized, controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Therefore, regarding EGb761® exposure, expecting a protective effect on the rate of dementia incidence in a delay of 3 to 6 years before dementia diagnosis would imply a direct effect of EGb761® on the neurodegenerative process itself during the more aggressive period of the pre-clinical phase, which is probably an over-optimistic hypothesis for the mechanism of action of this drug. In addition, a previous analysis of the PAQUID study has shown that EGb761® may increase the probability of survival in the elderly population [53]. Since age is the strongest risk factor for developing dementia demonstrated to date, the increased risk of developing dementia due to longer survival could also offset any possible beneficial effects of EGb761® on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regarding EGb761® exposure, expecting a protective effect on the rate of dementia incidence in a delay of 3 to 6 years before dementia diagnosis would imply a direct effect of EGb761® on the neurodegenerative process itself during the more aggressive period of the pre-clinical phase, which is probably an over-optimistic hypothesis for the mechanism of action of this drug. In addition, a previous analysis of the PAQUID study has shown that EGb761® may increase the probability of survival in the elderly population [53]. Since age is the strongest risk factor for developing dementia demonstrated to date, the increased risk of developing dementia due to longer survival could also offset any possible beneficial effects of EGb761® on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Poor performance on executive tests such as the Mini-Mental State Exam (Bassuk, Wypij, & Berkman, 2000;Dartigues et al, 2007) or the Short Portable Mental Status Questionnaire (Blazer, Sachs-Ericsson, & Hybels, 2005;Liang, Bennett, Sugisawa, Kobayashi, & Fukaya, 2003) tends to be associated with higher mortality risk, however the relationship has not always been found to be significant (Ganguli, Dodge, & Mulsant, 2002;Ostbye et al, 2006) and may be dependent on the length of the followup period (Ganguli et al, 2002; van Gelder, Tijhuis, Kalmijn, Giampaoli, & Kromhout, 2007). Performance on tests of crystallized intelligence, such as the National Adult Reading Test (Abas, Hotopf, & Prince, 2002;Anstey, Luszcz, Giles, & Andrews, 2001) or Raven's Mill Hill Vocabulary Scale (Rabbitt et al, 2002) tends to be robust to the effects of aging and is less likely to exhibit an association with mortality after health and social status are taken into account.…”
mentioning
confidence: 96%
“…Separating EGb 761 users from the other vasodilators gave similar odds ratios but did not reach statistical significance [70] . More recently, the analyses of the PAQUID Study concluded that EGb 761 (but not vasodilators) increases the survival time without dementia [71] .…”
Section: Treatment Effectiveness Of Antioxidantsmentioning
confidence: 99%